2016
DOI: 10.1371/journal.pone.0155338
|View full text |Cite
|
Sign up to set email alerts
|

Composing a Tumor Specific Bacterial Promoter

Abstract: Systemically applied Salmonella enterica spp. have been shown to invade and colonize neoplastic tissues where it retards the growth of many tumors. This offers the possibility to use the bacteria as a vehicle for the tumor specific delivery of therapeutic molecules. Specificity of such delivery is solely depending on promoter sequences that control the production of a target molecule. We have established the functional structure of bacterial promoters that are transcriptionally active exclusively in tumor tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The process of gene regulation involves transcription factors (TFs) binding to specific regions of the genome, such as proximal promoters or distal enhancers, to control gene expression [1]. TF binding to its target sites (TFBS) often occurs cooperatively, forming cisregulatory modules (CRMs) that are essential for effective and highly specific transcriptional regulation [2]. Collaborations between TFs, whether synergistic or antagonistic, impact gene specificity and regulatory flexibility during processes like tissue development or response to stimuli [3].…”
Section: Introductionmentioning
confidence: 99%
“…The process of gene regulation involves transcription factors (TFs) binding to specific regions of the genome, such as proximal promoters or distal enhancers, to control gene expression [1]. TF binding to its target sites (TFBS) often occurs cooperatively, forming cisregulatory modules (CRMs) that are essential for effective and highly specific transcriptional regulation [2]. Collaborations between TFs, whether synergistic or antagonistic, impact gene specificity and regulatory flexibility during processes like tissue development or response to stimuli [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, when it comes to the practical use of bioinformatic predictors, a researcher is often puzzled, first by selecting an appropriate bioinformatic program and then by a huge list of predictions that such programs usually produce. Once several programs are used to increase the chances of one at least finding a real functional motif, the list of predictions becomes too long for experimental verification ( Deyneko et al, 2016 ), even though independently found similar motifs are more likely to be correct and can be given higher priority ( Machanick and Kibet, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…By sorting and sequencing GFP expressing bacteria, they were able to identify tumor specific promoters [27]. In a follow-up paper, Deyneko et al then adapted these promoters and incorporated hypoxia sensing elements to build a synthetic tumor specific hypoxic promoter [28]. …”
Section: Introductionmentioning
confidence: 99%